Pondering Theory within Extension & Community Education: An Exploration of New Frontiers & Frameworks - Bryan Hains; Kristina Hains (Journal of International Agricultural and Extension Education, 2025)
A century after its humble beginnings, Cooperative Extension persists in being a strong foundation for rural communities within the United States, as well as a unique model for community education globally. Still, in our contemporary landscape, some would argue that if extension doesn’t evolve and transform, it could become irrelevant. As we look to the 21st Century, we propose five novel academic frameworks that, while respecting the traditions of extension, help to explain and move forward international extension and education processes within contemporary society. The innovative frameworks introduced are: the Emotional-Behavioral Influence Model, the Community Psychosocial Model, the Symbiotic Model of Community Reciprocity, Foundational Phases for Community Development and the Model of Urban Extension. Utilizing Extensionista as the setting in which to apply these frameworks, the authors demonstrate the utility of each model. Ultimately, these innovative frameworks are intended to augment and challenge the landscape of extension, both domestically and globally, into a more relevant future.
Keywords: Theory; Models; Frameworks; Extension; Community Education; Extensionista